2022
DOI: 10.30802/aalas-jaalas-21-000027
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pair-housing on Sleep Parameters Evaluated with Actigraphy in Female Rhesus Monkeys

Abstract: Rhesus monkeys are naturally social animals, and behavioral management strategies have focused on promoting pairhousingin laboratory settings as an alternative to individual or group housing. In humans, co-sleeping can have a major impact on bed partners’ sleep, raising the possibility that pair-housing also may influence sleep parameters in monkeys. In the present study, we investigated if pair-housing would impact home-cage partner’s sleep in female rhesus monkeys, and if nighttime separation using socializa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…We have previously reported that one 25 year old monkey in our colony showed longer baseline sleep latency and shorter baseline sleep duration compared to other monkeys (subject 98-003, Berro et al, 2021a ). However, other monkeys in our colony, as young as 9 years old, also show shorter sleep duration ( Berro et al, 2021a , 2022 ), demonstrating that, like humans, the sleep patterns of non-human primates may vary greatly between individual subjects.…”
Section: Discussionmentioning
confidence: 78%
“…We have previously reported that one 25 year old monkey in our colony showed longer baseline sleep latency and shorter baseline sleep duration compared to other monkeys (subject 98-003, Berro et al, 2021a ). However, other monkeys in our colony, as young as 9 years old, also show shorter sleep duration ( Berro et al, 2021a , 2022 ), demonstrating that, like humans, the sleep patterns of non-human primates may vary greatly between individual subjects.…”
Section: Discussionmentioning
confidence: 78%